PENGARUH PROGRAM DISKON, SUASANA TOKO, DAN PERIKLANAN TERHADAP LOYALITAS KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA KAFE TITIK KUMPUL REBORN SITUBONDO - Adhitya, Dhimas; Karnadi, Karnadi; Anshory, Muhammad Iqbal (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The purpose of this research is to determine the role of purchasing decisions in mediating discount programs, store atmosphere, and advertising on consumer loyalty at the Reborn Point Kumpul Cafe. The population in this research are consumers who make purchase transactions at the Point Kumpul Reborn CafÃ© Situbondo. The sampling technique used in this research is the probability sampling method using random sampling technique. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The research results show that the discount program has a significant positive effect on purchasing decisions, the store atmosphere has a significant positive effect on purchasing decisions, advertising has an insignificant positive effect on purchasing decisions, the discount program has a significant negative effect on consumer loyalty, the store atmosphere has an insignificant positive effect on consumer loyalty, Advertising has a positive but not significant effect on consumer loyalty, purchasing decisions have a positive and significant effect on consumer loyalty, discount programs have a positive and significant effect on consumer loyalty through purchasing decisions, discount programs have a positive but not significant effect on consumer loyalty through purchasing decisions, discount programs have a positive but not significant effect not significant to consumer loyalty through purchasing decisions.